Light-Mediated Inhibition of Colonic Smooth Muscle Constriction and Colonic Motility via Opsin 3 - Dan, William; Park, Ga Hyun; Vemaraju, Shruti; Wu, Amy D.; Perez, Kristina; Rao, Meenakshi; Berkowitz, Dan E.; Lang, Richard A.; Yim, Peter D. (Frontiers in Physiology, 2021)
Opsin photoreceptors outside of the central nervous system have been shown to mediate smooth muscle photorelaxation in several organs. We hypothesized that opsin receptor activation in the colon would have a similar effect and influence colonic motility. We detected Opsin 3 (OPN3) protein expression in the colonic wall and demonstrated that OPN3 was present in enteric neurons in the muscularis propria of the murine colon. Pre-contracted murine colon segments demonstrated blue light mediated relaxation ex vivo. This photorelaxation was wavelength specific and was increased with the administration of the chromophore 9-cis retinal and a G protein receptor kinase 2 inhibitor. Light mediated relaxation of the colon was not inhibited by L-NAME or tetrodotoxin. Furthermore, blue light exposure in the presence of 9-cis retinal decreased the frequency of colonic migrating motor complexes in spontaneously contracting mouse colons ex vivo. These results demonstrate for the first time a receptor mediated photorelaxation of colonic smooth muscle and implicate opsins as possible new targets in the treatment of spasmodic gastrointestinal dysmotility.